Prediction of Performance and Emission of CNG-Diesel Dual Fuel Engine using Response Surface Methodology - Shamsuddin, Muhammad Syahir; Zulkifli, Abd Fathul Hakim (Progress in Engineering Application and Technology, 2021)
Application natural gas for vehicle application through dual fuel system is well known. However, the conversion process especially for diesel engine application is challenging. In this study, the aim is to predict the performance and emission of CNG- diesel dual fuel engine using Response Surface Methodology (RSM). The test was performed between 1500 and 3500 rpm engine speed for each of CNG fraction between 0% to 40%. The evaluation of performance in term of brake torque, brake power and BSEC, while HC, CO and NOx was considered for exhaust emissions evaluation. Then, the prediction models were validated through confirmation test. Based on the RSM model, the performance of brake torque and brake power decreases with an increase of CNG substitution, while BSEC increase. As for exhaust emissions, both HC and CO increase greatly, while NOx emission decrease with an increase of CNG substitution. The confirmation test showed the prediction model is statistically significant. This concluded that, the dual fuel system engine shows an improvement in terms of BSEC and NOx compared to the diesel engine. Hence, contributing to the efficiency of the conversion process for dual fuel system.